Animated Films as a Tool for Vocabulary Acquisition in Vocational Education - Dini Andriani; Iskhak Said; R. Bunga Febriani (Journal of English Education Program (JEEP), 2026)
Vocabulary mastery is a crucial aspect of language learning, but it poses a challenge for vocational high school (SMK) students due to limited learning media. Previous studies have mostly used non-animated films as learning media, while animated films are still rarely explored. This study aims to investigate students' perceptions of using animated films as a vocabulary learning medium. The research employs a qualitative descriptive method, involving 20 participants from Grade X at SMK Al-Huda Turalak. Data collection techniques include observation and semi-structured interviews. The results of the study indicate that animated films can increase students' interest, engagement, and confidence in learning and using new vocabulary directly. Students can understand and remember new vocabulary through animated films, which are visual and contextual in nature and have proven to be effective. Therefore, animated films can be an attractive and effective alternative learning medium in the context of vocational schools.